Dampak Desentralisasi terhadap Kapabilitas Kepala Daerah (Studi Kasus Gubernur Riau Periode Tahun 2008-2013) - Setiawan, Ramadhani; Samin, Rumzi; Mahadiansar, Mahadiansar (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2018)
Leadership of the government (regional head) which is run centrally by the New Order regime was the forerunner for the implementation of the system of government that does not give an opportunity to the region to grow and progress. The occurrence of the reform era in which the shift change to decentralized government system that enhances the value of the substance of democracy. But the journey euphoria of regional autonomy as the Regional Head of the local authorities is getting stronger. Evidence of this, real happens area is the practices of KKN (corruption, Corruption and Nepotism) occur far in the achievement of decentralization expectations. The purpose of the study in this study is to discuss capability, even though each regional head is elected by the people. Researchers have done with qualitativ case studies in Riau province. The issue of inequality is specifically in terms of leadership obligations culminating from historical factors that provide a very large role for the leadership of the Regional Head as a regional authority. The issue is in which particular inequality in terms obligation culminating leadership of the historical factors that give a very big role for the leadership of the head area.